Naïve, Regulatory, Activated, and Memory Immune Cells Co-exist in PVATs That Are Comparable in Density to Non-PVAT Fats in Health - Kumar, Ramya K.; Jin, Yining; Watts, Stephanie W.; Rockwell, Cheryl E. (Frontiers in Physiology, 2020)
Perivascular adipose tissue (PVAT), the fat surrounding peripheral blood vessels, is protective and reduces the contraction of blood vessels in health. PVAT is composed of adipocytes, stromal cells and immune cells. Recent work supports eosinophils as one of the cell types key to the anti-contractile nature of PVAT in health. Hence, we hypothesized that there exists a basally activated immune cell community in healthy PVAT that is distinctly different from non-PVAT fats. PVATs were from around mesenteric resistance vessels (MRPVAT- white fat) and thoracic aorta (APVAT- brown fat). Non-PVATs included retroperitoneal (RP fat- white fat) and subscapular (SS fat- brown fat) while the spleen was a positive control. Tissues were harvested from adult male and female Sprague Dawley rats. Six primary immune cell types were identified in PVATs. T cells (CD4 and CD8), B cells, natural killer (NK) cells, macrophages, mast cells and neutrophils in the stromal vascular fraction of each fat were identified using 9-color flow cytometry. PVATs contained a higher number of total immune cells vs their respective non-PVAT fats in females. Females had a higher number of T cells in MRPVAT vs males. Females also had a greater number of T cells and total immune cells in APVAT vs males. Further, activation, differentiation and/or polarization of various immune cell types were similarly determined by flow cytometry. PVATs were similar to their respective non-PVAT fats in density of recently activated B cells (B220+ CD25+). However, MRPVAT in females had a higher number of naïve CD4 T cells vs MRPVAT in males and APVAT in females. MRPVAT also had denser naïve CD8 T cells vs APVAT in females. Overall, this research for the first time has identified a community of discrete populations of immune cells (naive/recently activated/regulatory/memory) in healthy PVATs. Contrary to our hypothesis, PVATs are more similar than different in density to their respective non-PVAT fats.